Yield Response of Irrigated Wheat Grown on Sandy Soil to Deep Tillage and Phosphorus Fertilizer - CHAUDHRY, MUHAMMAD S.; SHERIF, SHARAFEDDIN M. (The Libyan Journal of Agriculture, 2023)
The response of the semi-dwarf wheat, cultivar Sidi Mesri 1 (Triticum aestivum L.), to deep tillage and phosphorus fertilizer was studied on the sandy soil of Tripoli, the Libyan Jamahiriya. Subsoiling (50 cm deep) as compared to disk plowing (25 cm deep) and rotary cultivation (15 and 20 cm deep) gave significantly higher grain yield, spikes per plant, spikes per m2, number and weight of grains per spike, and 1000-grain weight. The response to disk plowing and rotary cultivators was not different. The addition of 80 kg P205/ha significantly enhanced the yield and its components. Higher dose showed no further effect. There was no interaction between the tillage depth and phosphorus for wheat yield and yield components. Occasional deep tillage and regular phosphorous fertilization seems necessary to increase wheat production in sandy soils of the coastal belt of the Libyan Jamahiriya.